2019
DOI: 10.1371/journal.pone.0223231
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufacini ameliorates experimental colitis via modulating the composition of gut microbiota

Abstract: BackgroundCinobufacini, the sterilized hot water extraction of dried toad skin, has been widely used in the treatment of inflammation and cancers. Recently we found cinobufacini could ameliorate dextran sulfate sodium (DSS)-induced colitis in mice, but the underlying mechanism was not fully understood. In current study, we explored the effect of cinobufacini on gut microbiota in DSS-induced acute colitic mouse model by pyrosequencing of colonic contents.MethodsC57BL/6 mice were supplied with normal or 3.0% DSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The genes in the metabolic pathways, including amino acid metabolism, terpenoids and polyketides, cofactors and vitamins, other amino acids, energy, and glycan biosynthesis metabolisms of the D group, were much lower than those in the N and DGPH groups ( p < 0.05). This could result in a decreasing metabolic rate in colitic mice, and it was also consistent with previous studies. , The genes related to environment information processing (Membrane Transport, Environmental Adatation) in the D group were up-regulated ( p < 0.05). Once the bacteria perceive the surrounding environmental changes, they will respond to these changes via such modulations like inflammatory reactions .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The genes in the metabolic pathways, including amino acid metabolism, terpenoids and polyketides, cofactors and vitamins, other amino acids, energy, and glycan biosynthesis metabolisms of the D group, were much lower than those in the N and DGPH groups ( p < 0.05). This could result in a decreasing metabolic rate in colitic mice, and it was also consistent with previous studies. , The genes related to environment information processing (Membrane Transport, Environmental Adatation) in the D group were up-regulated ( p < 0.05). Once the bacteria perceive the surrounding environmental changes, they will respond to these changes via such modulations like inflammatory reactions .…”
Section: Resultssupporting
confidence: 91%
“…This could result in a decreasing metabolic rate in colitic mice, and it was also consistent with previous studies. 61,62 The genes related to environment information processing (Membrane Transport, Environmental Adatation) in the D group were upregulated (p < 0.05). Once the bacteria perceive the surrounding environmental changes, they will respond to these changes via such modulations like inflammatory reactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species at the phylum level (e.g., Proteobacteria) could play a role in the pathogenesis of UC, leading to adhesion and invasion of intestinal epithelial cells, disruption of host defense, stimulation of the inflammatory response, alterations in the structure of intestinal microbiota, and ultimately, promote the onset of UC ( Bai et al, 2019 ). Furthermore, Escherichia , which is an IgA-coated bacteria at the genus level, is the dominant pathogen involved in the pathogenesis of UC ( Xu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidetes [29] , verrucomicrobia [30] and lachnospiraceae [31] would increase after treatment. These above bacteria have a certain inhibitory effect on in ammation, and play an important role in colitis and other intestinal diseases, which is consistent with our research results.Our data indicated that baicalin may reduce lachnospiraceae by reducing the diversity of ora, reducing the relative abundance of Firmicutes, increasing the relative abundance of Bacteroidetes, Proteobacteria and verrucomicrobia_ FCS020.…”
Section: Discussionmentioning
confidence: 99%